Combined effects of low-level laser therapy and human bone marrow mesenchymal stem cell conditioned medium on viability of human dermal fibroblasts cultured in a high-glucose medium. Issue 4 (May 2016) - Hendudari, Farzane; Piryaei, Abbas; Hassani, Seyedeh-Nafiseh; Darbandi, Hasan; Bayat, Mohammad
Abstract Low-level laser therapy (LLLT) exhibited biostimulatory effects on fibroblasts viability. Secretomes can be administered to culture mediums by using bone marrow mesenchymal stem cells conditioned medium (BM-MSCs CM). This study investigated the combined effects of LLLT and human bone marrow mesenchymal stem cell conditioned medium (hBM-MSCs CM) on the cellular viability of human dermal fibroblasts (HDFs), which was cultured in a high-glucose (HG) concentration medium. The HDFs were cultured either in a concentration of physiologic (normal) glucose (NG; 5.5 mM/l) or in HG media (15 mM/l) for 4 days. LLLT was performed with a continuous-wave helium-neon laser (632.8 nm, power density of 0.00185 W/cm2 and energy densities of 0.5, 1, and 2 J/cm2 ). About 10 % of hBM-MSCs CM was added to the HG HDF culture medium. The viability of HDFs was evaluated using dimethylthiazol-diphenyltetrazolium bromide (MTT) assay. A significantly higher cell viability was observed when laser of either 0.5 or 1 J/cm2 was used to treat HG HDFs, compared to the control groups. The cellular viability of HG-treated HDFs was significantly lower compared to the LLLT + HG HDFs, hBM-MSCs CM-treated HG HDFs, and LLLT + hBM-MSCs CM-treated HG HDFs. In conclusion, hBM-MSCs CM or LLLT alone increased the survival of HG HDFs cells. However, the combination of hBM-MSCs CM and LLLT improved these results in comparison to the conditioned medium.